Pengaruh Motivasi, Komunikasi, Dan Pelatihan Terhadap Kinerja Karyawan Pada PDAM Tirtana Di Medan Cabang Padang Bulan - Rosinta Romauli Situmeang; Yodia Friska Br Subakti; Andre Edward Panjaitan (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2022)
This research was conducted to examine and analyze the effect of motivation, communication and training on employee performance at PDAM Tirtanadi Medan Padang Bulan Branch. The nature of the research in this study is explanatory. The total population in this study was 84 and all of them were used as samples. The independent variables in this study consisted of motivation (X1), communication (X2) and training (X3), while employee performance was the dependent variable. Multiple linear regression analysis was used to examine the data. The results of the study indicate that partially and simultaneously, the variables of motivation, communication and training have a significant effect on employee performance at PDAM Tirtanadi Medan Padang Bulan Branch. Keywords: motivation, communication, training and performance